Editorial: Volume 3, Issue 2 - Kristy Archuleta; John E Grable (Journal of Financial Therapy, 2012)
In the mid-year issue of the Journal of Financial Therapy, we highlighted the many accomplishments the Journal has made in just three short years. The submissions to the Journal continue to grow, the quality of submissions is increasing, and the diversity of topics is expanding. For example, in this issue, topics of articles are not only specifically related to financial therapy, but also include: (a) financial literacy and social work, (b) financial coaching, and (c) financial trauma and tactical asset management. Seeing the Journal expand and grow is very exciting!
Keywords: financial therapy